Pembuatan Media PowerPoint Interaktif Sebagai Penunjang Pembelajaran Materi Sistem Peredaran Darah - Masra Latjompoh; Frida Maryati Yusuf; Elya Nusantari; Yulantika Stiosarint; Altri Rahmadhani Lanio; Andini Pratiwi M Mahmud (Educatio, 2025)
The purpose of this study is to create interactive learning media using Microsoft PowerPoint about the human circulatory system. This media is designed as an alternative learning resource that is interesting, easy to understand, and rich in visuals. The development process follows the ADDIE model, but this study only reaches the development stage without being tested directly in class. The media creation process is the main subject of this study, which employs a qualitative descriptive methodology. The PowerPoint created is equipped with navigation features with hyperlinks, visual images, explanatory videos, and interactive quizzes. These features aim to increase students' interest in learning, facilitate understanding of the material, and support independent learning, both online and offline. The results of this development stage indicate that this media has the potential to support science learning, especially the circulatory system material, because it combines visual and interactive elements that can increase student motivation and learning outcomes. The next stage is recommended to implement and evaluate the effectiveness of this media in the classroom. Keyword: Development, Media, PowerPoint